RANCANG BANGUN PERANGKAT MONITORING DENYUT JANTUNG DAN SUHU TUBUH - Saputra, Erwin Adias; Subito, Mery; Dodu, A.Y. Erwin (MEKTRIK)
Today, the development of science leads to the development of technologies intended to facilitate all the activities and work of human. In medical field, the used technology seem’s to be more practical, effective and efficient. In medical world, physical or clinical examination is a process undertaken by a medical expert to examine the patient's body so that it can be found clinical signs of disease. Now the use of technology in medical field is quite expensive so it is still much less practical in using of technology, effectively and efficiently. It is needed a technology that can automatically record one’s heart rate and temperature conditions so that facilitate patient medical record activity. By apply is the technology that can automatically show the value of the results of the clinical examination is expected to improve the process examination of the patient. By using a microcontroller that can change the amount of voltage into a digital value, photodiode sensors to measure heart rate and LM35 to measure the body temperature of the patient. The measured value sent by sensor will be treated and displayed on computer. The measurement results are in units that suitable to measured units like bpm (beats per minute) for heart rate and temperature oC for temperature. Results are displayed on the GUI (Graphic User Interface) in computer graphics and realtime with a value corresponding to the value generated by the sensor. The equipment testing results of error rate from heart beat sensor is 2.9% and temperature sensor is 0.51%.